(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article aims to think about the writing of the body in the pedagogical scene, stressing the theatrical dimension of teaching and its relationship with knowledge. In this sense, it seeks to articulate the theatricality of the teaching craft with the knowledge of the body that is written subjectively in the experience of the subjects of education. This knowledge of the body comes from the patient exercise of teaching and can produce transformative effects on ways of being, saying and acting. The voice, gaze and gesture that are written in the pedagogical scene make up this knowledge of the body, which can reconfiguring the sharing of the sensible in everyday school life and symbolically marking other bodies through the affections it produces and circulates.